2000
DOI: 10.1088/0268-1242/15/6/314
|View full text |Cite
|
Sign up to set email alerts
|

Band offset predictions for strained group IV alloys: Si1-x-yGexCyon Si(001) and Si1-xGexon Si1-zGez(001)

Abstract: The band offsets for strained Si 1−x−y Ge x C y layers grown on Si(001) substrate and for strained Si 1−x Ge x layers grown on fully relaxed Si 1−z Ge z virtual substrates are estimated. The hydrostatic strain, the uniaxial strain and the intrinsic chemical effect of Ge and C are considered separately. Unknown material parameters relative to the latter effect are chosen to give the best agreement with the available experimental results for Si 1−x Ge x and Si 1−y C y layers on Si. As a general trend concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 50 publications
(65 reference statements)
0
28
0
Order By: Relevance
“…Therefore, process margin for SiGe HBT fabrication can be relaxed. On the other hand, it has been reported that the bandgap and the band offsets with respect to the conduction band and valence band sensitively varies with C contents and strain in Si 1ÀxÀy Ge x C y films [151][152][153][154][155][156][157][158][159][160][161]. On the basis of the control over the band alignment in the Si 1ÀxÀy Ge x C y hetero structures, Si 1ÀxÀy Ge x C y epitaxial films were applied to channel layers in MOSFET [162,163], high-electron mobility transistor (HEMT), and optical devices [164][165][166].…”
Section: Formation Of Sigec Alloysmentioning
confidence: 99%
“…Therefore, process margin for SiGe HBT fabrication can be relaxed. On the other hand, it has been reported that the bandgap and the band offsets with respect to the conduction band and valence band sensitively varies with C contents and strain in Si 1ÀxÀy Ge x C y films [151][152][153][154][155][156][157][158][159][160][161]. On the basis of the control over the band alignment in the Si 1ÀxÀy Ge x C y hetero structures, Si 1ÀxÀy Ge x C y epitaxial films were applied to channel layers in MOSFET [162,163], high-electron mobility transistor (HEMT), and optical devices [164][165][166].…”
Section: Formation Of Sigec Alloysmentioning
confidence: 99%
“…This type of biaxial strain introduces a splitting of degenerate bands [1][2] which results, for both electrons and holes, in smaller in-plane effective mass and reduced intervalley scattering yielding improved transport properties. N-type Si/SiGe modulation-doped FETs (MODFETs) have demonstrated low noise figure and high cut-off and maximum oscillation frequencies [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…A coherent strain applied along direction ͑001͒ lifts at least partially the degeneracy of conduction and valence bands. 35 In case of tensile strain the energy position of normal ⌬ valleys shifts down, whereas that of parallel valleys shifts up, as illustrated in Fig. 6.…”
Section: Heterojunction Mos Structuresmentioning
confidence: 90%
“…33,34 A similar design of n-type MOSFET requires a tensile strained layer to create a convenient conduction band offset. 35 Two types of heterostructures may be used in this order. Classically, a tensile strain is obtained by growing a Si layer on a Si 1Ϫx Ge x virtual substrate.…”
Section: Heterojunction Mos Structuresmentioning
confidence: 99%